A role for bone marrow–derived cells in diabetic nephropathy. Issue 3 (29th November 2018) - Nobuta, Hiroshi; Katagi, Miwako; Kume, Shinji; Terashima, Tomoya; Araki, Shin-Ichi; Maegawa, Hiroshi; Kojima, Hideto; Nakagawa, Takahiko
ABSTRACT: Diabetes mellitus causes systemic disorders. We previously demonstrated that diabetic condition forced bone marrow–derived cells (BMDCs) to express TNF‐α, leading to the development of diabetic neuropathy in mice. Here, we hypothesized that these abnormal BMDCs are also involved in diabetic nephropathy. To test our hypothesis, mice were irradiated to receive total bone marrow (BM) from the transgenic mice expressing green fluorescent protein before diabetes was induced by streptozotocin. Confocal microscopy showed that the diabetic glomerulus had more BMDCs compared with the nondiabetic glomerulus. Most of these cells exhibited endothelial phenotypes, being negative for several markers, including podocin (a maker of podocyte), α8 integrin (mesangial cell), CD68, and F4/80 (macrophage). Next, the total BM of diabetic mice was transplanted into nondiabetic mice to examine if diabetic BM per se could cause glomerular injury. The recipient mice exhibiting normal glycemia developed albuminuria and mesangial expansion with an increase in capillary area. The number of BMDCs increased in the glomerulus of the recipient mice. These cells were found to exhibit the endothelial phenotype and to express TNF‐α. These data suggest that diabetic BMDCs per se could initiate glomerular disease. Finally, eNOS knockout mice were used to examine if residential endothelial injury could attract BMDCs into the glomerulus. However, endothelial dysfunction due to eNOS deficiency failed to attract BMDCs into the glomerulus. In summary, BMDCs may be involved in the development of diabetic nephropathy.—Nobuta, H., Katagi, M., Kume, S., Terashima, T., Araki, S., Maegawa, H., Kojima, H., Nakagawa, T. A role for bone marrow‐derived cells in diabetic nephropathy. FASEB J. 33, 4067–4076 (2019). www.fasebj.org